PENGELOLAAN MANAJEMEN HUBUNGAN MADRASAH DENGAN MASYARAKAT DALAM PENYELENGGARAAN PENDIDIKAN - Khomsinnudin (Jurnal Tawadhu, 2023)
The interaction between educational institutions and the community has recently been less friendly. The gap between madrasas and the community as customers of education influences people's assumptions and opinions about the unfavorable image of educational institutions, which is one of the contributing factors. Another factor that clearly influences is the role of public relations in an organization. A relationship manager has to take many steps to improve the cooperation between the madrasah and the community, including the concepts of management, planning, implementation and evaluation. Collaboration between madrasas and parents of students is expected to produce quality education. There is a concept that requires communication to influence others and get a positive response. The immediate response from the recipient of the news is only a sound or problems arise during communication because the communicant has received a different message from the communicator's message. Increasing community and government accountability, establishing strategies to monitor development results.